Telegram Discourse on The 2017 Iran’s Presidential Election - Hossein Kermani (Department of Communications, Universitas Islam Indonesia, 2020)
This paper explores the discourse in Telegram during the Iran’s 2017 election period. Recently, Telegram has become the most popular social media in Iran, playing a significant role in recent social and political events. This paper examines the highest-ranking posts to provide a better understanding of Telegram posts’ characteristics, dynamics, and potentials for producing the new discourses or reinforcing the existing ones. The materials of this study were gathered from the 620 most-viewed posts during the election period. The data were analyzed mainly with quantitative content analysis and completed with ethnographic content analysis. This study finds that counter discourses are not shaped in Telegram and the most viewed posts mainly reproduce and reinforce the dominant discourses. This finding also clarifies how the content circulation is affected by the national political events, such as the election. Keywords: Telegram, Iran, presidential election, content analysis, discourse analysis.